Healthy Kitchen Moengko: A Community Empowerment Initiative for Improving Child Nutrition in PosoHealthy Kitchen Moengko: A Community Empowerment Initiative for Improving Child Nutrition in Poso - Achmad Budiawan Putra; Fahmi Khatib Rahman; Ringga Permana; Andi Ferina Herbourina Bonita (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
The Moengko Healthy Kitchen is a corporate social responsibility initiative by PT Pertamina Patra Niaga FT Poso, addressing child malnutrition in Moengko, Poso Regency. Using social mapping, descriptive analysis, and community interviews, the program identified 24 undernourished children in the area. Interventions focused on supplementary feeding, supported by local women farmer groups, combined with health education on parenting, early marriage prevention, and anti-drug campaigns. Six undernourished children received direct supplementary food interventions, with five showing nutritional improvement, though still categorized as undernourished. The program empowered Posyandu cadres and local farmers, fostered sustainable community-based food production, and created a model for future CSR-driven nutrition interventions